Safety and Security of Female Students in Public Transport: A Case Study of a State University in Sri Lanka - Tharsika, K.; Sayanthan, B. (University of Jaffna, 2024)
Purpose: Despite the significant role women play in developing human capital and advancing a nation's development, safety, and security challenges arise when commuting by public transport to university for higher education. This study aims to assess the specific safety and security challenges faced by female students using public transportation at a state university in Sri Lanka and propose solutions to improve their protection. Design/Methodology/Approach: The study employs a quantitative survey method, distributing questionnaires to 110 randomly selected female students to gather data on their experiences regarding safety and security while using public transportation. This approach aims to assess the specific challenges faced by female students in this context. The questionnaire was piloted and validated to ensure reliability and accuracy in capturing the students' experiences Findings: The research revealed that a significant percentage of female students experience verbal (62%) and physical harassment (79%) while using public transport. The lack of awareness of reporting mechanisms and ineffective legal measures contribute to the continuation of such incidents, affecting their mental well-being and academic performance. Research Limitations: The research is limited to one state university and may not fully represent the experiences of female students in other regions or institutions. Further studies incorporating qualitative methods could provide a more comprehensive understanding of individual narratives. Implications: The findings emphasize the need for policy reforms, including the implementation of awareness programs, effective reporting mechanisms, and stricter legal actions against offenders. These reforms, developed in collaboration between universities and transportation authorities, would increase safety and contribute significantly to the academic and personal growth of female students.
Keywords: Gender-based harassment; Harassment in public transport; Policy reforms and academic performance